The Committee on Public Information: A transmedia war propaganda campaign - Benson Krystina (Cultural Science)
This article summarises a PhD dissertation of the same name. It develops an understanding of how propaganda entered journalism and popular culture in the United States during World War I through an examination of materials created by the Committee on Public Information (CPI). Three CPI divisions were studied: The Division of News, the Four Minute Men, and the Division of Pictorial Publicity. The methodology of archival contextualisation was created, bringing together the methods of close reading, discourse-historical contextualisation, and Piercian semiotics. A summary of relevant literature is interspersed with thematic historical developments that impacted the relationship between propaganda, journalism and popular culture. This review outlines a gap in knowledge about the archival materials as well as the relationship between propaganda, journalism and popular culture from this period. A discussion about how the expectations of persuasion, truth and amusement relate to each other when mediated in culture, using Lotman’s concept of the semiosphere further develops an understanding of propaganda as a cultural system in relation to other cultural systems – in this case, journalism and popular culture. Findings from the study include that the CPI created a transmedia war propaganda campaign, which enabled propaganda to successfully draw entertainment value from popular culture and credibility from journalism in order to influence public opinion.